FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN NYERI MENSTRUASI (DISMINORE) PADA REMAJA PUTRI - Dina Permata Sari; Titin Dewi Sartika; Erma Puspitasari; Chairuna (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Menstruation is endometrium releasing process included with bleeding and happened many times every month except in pregnancy. According to the World Health Organization (WHO) the number of disminore in the world is very large, the average more than 50 % of women in every country suffer from disminore. The aims of this research is to find out the correlation of menarche age, length of menstruation and family history with menstrual pain incident to the teenage girl of Social Class XI of Islamic Senior High School Number 1 year 2021. The method of this research used Survey Analitic with Cross Sectional approach. The populations in this research are all schoolgirls of Class XI of Islamic Senior High School Number 1 Palembang year 2021/2022, which amount 168 pepole. Big samples of this research are 63 respondents whom taken from using Stratified random sampling. Data collecting used questioner sheet. Data analysis used univariate and bivariate by using chi square test. Results : respondents who experience menstruation pain are 35 (55,6%) teenagers, normal menarche age respondents are 45 (71,4%) teenagers, respondents who experience normal menstruation length are 50 (79,4%) teenagers, respondents who have no disminore experiences family history are 42 (66,7%) teenagers. Bivariate result known that there is menarche age (length of menstruation) and family history (with menstruation pain incident to the teenage girls of Class XI of Islamic Senior High School Number 1 year 2021. The conclusion that there is correlation between menarche age, length of menstruation and family history with menstruation pain incident to the teenage girls of Social Class XI of Islamic Senior High School Number 1 year 2021. Suggestion : expected to the school authorities to cooperate with Health agencies to give counseling to the schoolgirls about female reproduction especially disminore.